B2 precipitates formation in Al-containing CoCrFeMnNi-type high entropy alloy. Issue 1 (January 2021) - Klimova, M; Shaysultanov, D; Semenyuk, A; Zherebtsov, S; Salishchev, G; Stepanov, N
Abstract: The non-equiatomic Al7.5 Co21.75 Cr5.5 Fe21.75 Mn21.75 Ni21.75 high entropy alloy was studied. After cold rolling and annealing at 700-900 °C, a dual-phase ultrafine-grained structure composed of the partially recrystallized fcc matrix and B2 particles was produced; complete recrystallization of the fcc phase was observed after annealing at 1000 °C. The B2 precipitates formation provided a significant strengthening of the alloy in comparison with the single-phase state. The alloy demonstrated an attractive combination of mechanical properties, presenting yield and ultimate tensile strengths of 900 MPa and 1200 MPa, respectively, along with a ductility of 22%.